Alpha Interferon and Ribavirin Combination Therapy of Chronic Hepatitis D - Kaymakoglu, Sabahattin (American Society for Microbiology, 2005)
The success of alpha interferon (IFN-α) monotherapy for the treatment of chronic hepatitis D is very limited. In this study, the efficacy of IFN-α and ribavirin combination therapy for chronic hepatitis D was investigated. Nineteen patients (15 males; mean age ± standard deviation, 36.8 ± 12.8 years) with chronic hepatitis D who were treated with IFN-α2b (10 million U, three times/week, subcutaneously) and ribavirin (1,000 to 1,200 mg/day, orally) for 24 months were studied. All patients had compensated liver disease (15 were precirrhotic), elevated transaminase levels, and hepatitis D virus RNA positivity at baseline. Genotypic analyses revealed hepatitis D virus genotype I and hepatitis B virus genotype D. All patients completed the 24 months of treatment and at least 6 months (7 to 19 months) of a follow-up period. Biochemical responses were observed in eight patients (42.1%) at the end of treatment and in seven patients (36.8%) at the end of follow-up. Eight patients (42.1%) at the end of treatment and four patients (21%) at the end of follow-up had virological responses. In conclusion, combination treatment of IFN-α and ribavirin for chronic hepatitis D is not able to induce virological responses at a sufficient rate, despite its partial effectiveness in improving biochemical responses, and is not superior to IFN-α monotherapy.